Performance of biotrickling filters for hydrogen sulfide removal under starvation and shock loads conditions - Zhang, Lan-he; Meng, Xiu-li; Wang, Ying; Liu, Li-dan (Journal of Zhejiang University. B. Science, 2009)
In the industrial operation of biotrickling filters for hydrogen sulfide （H2S） removal, shock loads or starvation was common due to process variations or equipment malfunctions. In this study, effects of starvation and shock loads on the performance of biotrickling filters for H2S removal were investigated. Four experiments were conducted to evaluate the changes of biomass and viable bacteria numbers in the biotrickling filters during a 24-d starvation. Compared to biomass, viable bacteria numbers decreased significantly during the starvation, especially when airflow was maintained in the absence of spray liquid. During the subsequent re-acclimation, all the bioreactors could resume high removal efficiencies within 4 d regardless of the previous starvation conditions. The results show that the re-acclimation time, in the case ofbiotrickling filters for H2S removal, is mainly controlled by viable H2S oxidizing bacteria numbers. On the other hand, the biotrickling filters can protect against shock loads in inlet fluctuating H2S concentration after resuming normal operation. When the biotrickling filters were supplied with H2S at an input of lower than 1700 mg/m^3, their removal efficiencies were nearly 98% regardless of previous H2S input.